Congestion Relief of Contingent Power Network with Evolutionary Optimization Algorithm - Sandip Chanda; Abhinandan De Abhinandan De (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2012)
This paper presents a differential evolution optimization technique based methodology for congestion management cost optimization of contingent power networks. In Deregulated systems, line congestion apart from causing stability problems can increase the cost of electricity. Restraining line flow to a particular level of congestion is quite imperative from stability as well as economy point of view. Employing ‘Congestion Sensitivity Index’ proposed in this paper, the algorithm proposed can be adopted for selecting the congested lines in a power networks and then to search for a congestion constrained optimal generation schedule at the cost of a minimum ‘congestion management charge’ without any load curtailment and installation of FACTS devices. It has been depicted that the methodology on application can provide better operating conditions in terms of improvement of bus voltage and loss profile of the system. The efficiency of the proposed methodology has been tested on an IEEE 30 bus benchmark system and the results look promising.